2010
DOI: 10.2337/dc09-2260
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Once-Daily Liraglutide From Twice-Daily Exenatide Further Improves Glycemic Control in Patients With Type 2 Diabetes Using Oral Agents

Abstract: OBJECTIVETo evaluate efficacy and safety of switching from twice-daily exenatide to once-daily liraglutide or of 40 weeks of continuous liraglutide therapy.RESEARCH DESIGN AND METHODSWhen added to oral antidiabetes drugs in a 26-week randomized trial (Liraglutide Effect and Action in Diabetes [LEAD]-6), liraglutide more effectively improved A1C, fasting plasma glucose, and the homeostasis model of β-cell function (HOMA-B) than exenatide, with less persistent nausea and hypoglycemia. In this 14-week extension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 11 publications
3
145
0
3
Order By: Relevance
“…Some reports showed the incidence of nausea (28% with EX vs. 25.5% with LIR) and vomiting (9.9% with EX vs. 6.0% with LIR) in patients with EX were higher than in patients with LIR. 41,42 However, little direct evidence exists about the difference among GLP-1 RAs in effects on GI AEs, and there is still a lack of convincing evidence on how these new GLP-1 RAs (Albi, TAS, and LIX) have more risk on GI AEs than EX and LIR.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed the incidence of nausea (28% with EX vs. 25.5% with LIR) and vomiting (9.9% with EX vs. 6.0% with LIR) in patients with EX were higher than in patients with LIR. 41,42 However, little direct evidence exists about the difference among GLP-1 RAs in effects on GI AEs, and there is still a lack of convincing evidence on how these new GLP-1 RAs (Albi, TAS, and LIX) have more risk on GI AEs than EX and LIR.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study also reported substantial weight loss in liraglutide-treated patients compared to placebo, it is noteworthy that observed reductions in SBP occurred before weight loss. In another setting, patients switching to once-daily liraglutide after 26 weeks of twicedaily exenatide experienced reductions in SBP of 3.8 mm Hg after 14 weeks of liraglutide [19]. For those continuing on liraglutide, a reduction of 2.2 mm Hg SBP was observed.…”
Section: Glp-1 and Blood Pressurementioning
confidence: 95%
“…Liraglutide also had significantly greater reductions in HbA1c than exenatide (-1.1% vs. -0.8%, p < 0.0001) [25]. Results from a 14-week extension of this trial demonstrated additional benefits in glycemic control (HbA1c -0.3%; p < 0.001), as well as a further reduction in SBP (-3.8 mmHg; p < 0.001), and additional weight loss (-0.9 kg; p < 0.001) in 186 patients who switched from exenatide to liraglutide [128].…”
Section: Liraglutidementioning
confidence: 99%
“…Results from a 14-week extension of this trial demonstrated additional benefits in glycemic control (HbA1c -0.3%; p < 0.001), as well as a further reduction in SBP (-3.8 mmHg; p < 0.001), and additional weight loss (-0.9 kg; p < 0.001) in 186 patients who switched from exenatide to liraglutide [128]. Data from four clinical trials of liraglutide in combination with one or two oral therapies (metformin plus sulfonylurea or thiazolidinedione) achieved HbA1c reductions of 1.0% to 1.5% for liraglutide 1.2 mg (all reductions were significant vs. placebo), and 1.0% to 1.5% for 1.8 mg (all reductions were significant vs. placebo).…”
Section: Liraglutidementioning
confidence: 99%